Childhood Adversities and Individual Responsibility as Explanations for Criminality in Incarcerated Young Men's Narratives. Issue 9 (2nd September 2022) - Franzén, Anna G.; Gottzén, Lucas
ABSTRACT: Childhood adversities, such as abuse, neglect and parental alcohol and substance abuse, has been linked to higher rates of youth delinquency. Drawing on interviews with 33 young male offenders, incarcerated in Swedish prisons, this paper analyzes how they narrate their experiences of growing up, and particularly how they make sense of their childhood adversities in light of their present situation as incarcerated and convicted of serious crime. Three forms of narratives are identified: stories of childhood adversities affecting the present delinquent self; narratives where "the problem child" serves as the link between childhood and present self; and "broken narratives" where childhood adversities are depicted as not associated with the present self at all. The majority of the young men draw upon the latter two of these narrative types. The analyses conclude that in both of them the young men avoid presenting that their childhood adversities have affected their contemporary selves and criminal behavior, but rather emphasize individual responsibility tied both to street masculinity and to a discourse of responsibilization.